Exploring Physical Phenomena - van Zee, Emily; Gire, Elizabeth (Open textbook library., 2019)
This course is intended for prospective and practicing elementary and middle school teachers. By exploring physical phenomena in class, you will learn science in ways in which you are expected to teach science in schools or in informal settings such as afterschool programs, youth group meetings, and museum workshops. This course also is appropriate for general science students and others interested in exploring some of the physical phenomena underlying global climate change. The theme for the course is: What happens when light from the Sun shines on the Earth? The emphasis is on questioning, predicting, exploring, observing, discussing, reading, and writing about what one thinks and why. This first unit focuses on exploring the nature of light phenomena. Among the unit’s many goals are two primary ones: to learn about light phenomena and to learn about ways to foster science learning for yourself and others such as your family, friends, and students.